2018
DOI: 10.1002/hep4.1296
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis as a Possible Risk Factor in the Development/Severity of Acute Alcoholic Hepatitis

Abstract: Bacterial infection is frequently observed in patients with alcoholic liver disease (ALD). We examined a possible role of Porphyromonas gingivalis in the development/progression and severity of disease in patients with acute alcoholic hepatitis (AAH). Plasma specimens from 47 patients with AAH (16 moderate, Model for End‐Stage Liver Disease [MELD] score <20]; 31 severe, MELD score >20) and 22 healthy controls (HCs) were collected. Clinical, drinking history (lifetime drinking history [LTDH]), and demographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…These results were in agreement with the study conducted in Jordan 39 . Porphyromonas gingivalis is a risk factor for alcohol‐related hepatitis, 40 indicating that Porphyromonas genus is associated with alcohol drinking. Since oral hygiene habits are mainly related to age, 41 the association network between age and salivary microbial taxa was also found to be similar to that of OHI.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in agreement with the study conducted in Jordan 39 . Porphyromonas gingivalis is a risk factor for alcohol‐related hepatitis, 40 indicating that Porphyromonas genus is associated with alcohol drinking. Since oral hygiene habits are mainly related to age, 41 the association network between age and salivary microbial taxa was also found to be similar to that of OHI.…”
Section: Discussionmentioning
confidence: 99%
“… 91 More recently, a study showed an association of P. gingivalis with acute alcoholic hepatitis (AAH) development/progression. 88 Patients with severe AAH showed significantly higher plasma levels of IgG, IgA, and IgM against two P. gingivalis strains (W83 and 33277) compared to healthy controls. Patients with moderate AAH also had significantly elevated anti- P. gingivalis IgA concentrations of both strains compared to healthy controls.…”
Section: Oral Microbiota Dysbiosis and Aldmentioning
confidence: 91%
“… 84 , 85 P. gingivalis can also be swallowed with saliva and enter the intestine, 86 , 87 causing liver disease via the gut-liver axis. 88 Periodontitis is associated with increased hepatic fibrosis in human subjects with NAFLD and P. gingivalis worsens steatohepatitis in mice fed a high-fat diet. Interestingly, a program of dental hygiene therapy improved NAFLD in humans.…”
Section: Oral Microbiota Dysbiosis and Aldmentioning
confidence: 99%
“…Hepatic tissues from patients with severe alcoholic hepatitis were obtained from the Resources Center of Johns Hopkins University. Details of characterizations and eligibility of human subjects have been described previously [25–27] and also in Supplementary materials and methods.…”
Section: Methodsmentioning
confidence: 99%